Implementasi Budaya Toleransi Beragama melalui Pembelajaran Pendidikan Agama Islam berwawasan Multikultural - Ansari Ansari (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2019)
Islamic religious education is an alternative solution for all people, by respecting each other, respecting and raising each other's caring without having to disturb their respective beliefs. Maintaining a culture of religious tolerance in providing Islamic religious learning must be applied by showing: 1). Mutual respect and respect in religion by instilling the values ??and understanding of science to not hate each other among religious communities; a) Togetherness; b) Activities that promote a culture of tolerance; c) Be universal and do not discriminate between students; d) Upholding respect and respect; e) Give opportunity to all students to get religious learning in accordance with their respective beliefs; 2). Applying the learning of Islamic education in the culture of religious tolerance by covering several factors, namely: a) The creation of a comfortable and conducive learning atmosphere; b) School activities run smoothly and have a high tolerance; c) The creation of a culture of mutual respect, respect and acceptance of differences; d) The realization of harmony in religious life in differences; e) The implementation of worship is carried out well; f) Avoiding conflict and division.